The Role Of Financial Literacy As A Mediator Between The Influence Of Lifestyle And The Use Of Financial Technology On The Consumptive Behavior Of Students At Institut Teknologi Petroleum Balongan - Tasi'ah, Tasi'ah; Sulaiman, Eman; Masyhud, Herman (Jurnal Ekonomi, 2024)
This study explores the role of financial literacy as a mediator in the relationship between lifestyle, the use of financial technology, and the consumptive behavior of students at Institut Teknologi Petroleum Balongan. Employing a quantitative research design, data were collected through surveys and analyzed using the Smart PLS 4.0 program. The results from partial variable testing indicate that lifestyle does not have a significant direct influence on students' consumptive behavior, as the calculated t-value did not exceed the critical t-value, leading to the acceptance of the null hypothesis. In contrast, financial technology has a significant impact on consumptive behavior, with a calculated t-value of 6.977, exceeding the critical t-value of 1.968, and a significance level of 0.000 (p < 0.1). Additionally, both lifestyle and financial technology significantly influence financial literacy, with t-values of 5.079 and 4.959 respectively, both greater than the critical t-value, and significance values below the α level of 0.1. However, financial literacy was not found to significantly affect consumptive behavior, as indicated by a t-value of 1.017, which is less than the critical t-value, and a significance level of 0.309 (p > 0.1). These findings suggest that while financial technology directly shapes consumptive behavior, lifestyle primarily affects financial literacy without directly influencing consumptive habits. The results imply that enhancing financial literacy may not directly mitigate consumptive behavior; instead, it could be more effective in guiding lifestyle-related financial decisions.